196k views
3 votes
(X^25)^-6/(x-^3)^48 simplify

(X^25)^-6/(x-^3)^48 simplify-example-1
User Felix Ogg
by
5.2k points

2 Answers

4 votes

Answer:


x^(-6)

Explanation:

using the rules of exponents


(a^m)^(n) =
a^(mn)


(a^(m) )/(a^(n) ) =
a^(m-n)

simplifying numerator/ denominator


(x^(25(-6)) )/(x^(-3(48)) )

=
(x^(-150) )/(x^(-144) )

=
x^(-150-(-144))

=
x^(-150+144) =
x^(-6)



User Mantas Astra
by
5.1k points
5 votes


\frac{1}{ {x}^(6) }
hope this is what you are looking for
User Samer Murad
by
5.3k points